Implementing the WiPo architecture - Florian Stahl; Adrian Godde; Bastian Hagedorn; Bastian Köpcke; Martin Rehberger; Gottfried Vossen (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2014)
Information available online has exploded over the last 20 years. However this lead to the phenomenon known as information overload, making it harder and harder for organisations and individuals to find information that is really relevant to them. We previously have proposed a solution to this problem by presenting a framework that does not answer queries solely based on a pre-assembled index, but based on a subject-specific database that is sourced from the Internet, curated by domain experts, and dynamically generated based on vast user input. In this paper we describe our prototypic implementation of an information platform that delivers high quality information to users, achieved by means of curation.
Keywords: 650; Web in Your Pocket; Information Provisioning; High Quality Information; Curation; Architecture